Dark Triad and CWB : Incivility Mediation and Leadership Moderation in the Pharmaceuticals Industry - Mishra, Priya; Kulshreshtha, Kushagra (Prabandhan: Indian Journal of Management, 2026)
Purpose : This study examined the relationship between Dark Triad personality traits and counterproductive work behavior (CWB) in the pharmaceutical industry, while also exploring the mediating role of workplace incivility (WI) and the moderating role of servant leadership (SL). Methodology : A cross-sectional survey design was employed to collect data from 409 participants, and the data were analyzed using structural equation modeling. Findings : The findings revealed that Machiavellianism, psychopathy, and narcissism were significant predictors of CWB, with WI partially mediating these relationships. SL also moderated these associations, influencing the strength of the link between dark traits and CWB. Implications : The results suggested that pharmaceutical organizations should incorporate personality risk assessments, strengthen SL capabilities, and implement practices that reduce WI. Originality : This study contributed by integrating personality traits, workplace dynamics, and leadership perspectives into a comprehensive and unified framework.